Immunoglobulin containing cells in terminal ileum and colorectum of patients with arthritis related gut inflammation. Issue 7 (July 1988) - Cuvelier, C; Mielants, H; De Vos, M; Veys, E; Roels, H
Abstract : In 40 distal ileal and 40 colonic biopsies of arthritic patients mostly without gastrointestinal symptoms, but with histological evidence of acute or chronic inflammation of the gut, the number of immunoglobulin (Ig) containing plasma cells was studied morphometrically using a peroxidase antiperoxidase technique. Compared with controls, the ileal mucosal biopsies showed an increase of IgA and IgG in acute ileitis. In chronic ileitis there was an increase of IgA, IgG, and IgM similar to Crohn's disease. In colonic biopsies there was a significant increase of all immunoglobulin classes in acute inflammation. In chronic inflamed mucosa there was also an increase of all three Ig classes. The Ig distribution, however, was significantly different in acute and chronic colitis. These findings give immunohistochemical evidence of the existence of two different types of inflammation related to reactive arthritis or the peripheral joint involvement of ankylosing spondylitis. The Ig pattern in acute colitis is similar to that found in infectious colitis, suggesting an enterobacterial origin of the arthritis in this group of patients although bacteriological and serological investigations were negative. In the chronic type of arthritis related ileocolitis, the pattern of Ig containing cells is similar to that found in Crohn's disease but different from infectious and ulcerative colitis, which makes the hypothesis that a great number of these arthritis patients suffer from asymptomatic or subclinical Crohn's disease acceptable.